Intellectual Property in the Global Arena Jurisdiction, Applicable Law, and the Recognition of Judgments in Europe, Japan and the US - Basedow, Jürgen; Kono, Toshiyuki; Metzger, Axel (Mohr Siebeck, 2010)
Geistiges Eigentum auf der globalen Ebene. Rechtsprechung, angewandtes Recht und die Anerkennung von Entscheidungen in Europa, Japan und den USA.
PublicationDate: 20100803
Keywords: Japan -- Private International Law -- Intellectual Property -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht -- Internationales Privatrecht -- Commerce Law, Corporate Law, Business Law, Tax Law -- Array